Description of a new Caliphaea species from Yunnan, China (Odonata: Calopterygidae) - Zhang, Hao-Miao; Hämäläinen, Matti (Zootaxa, 2020)
A new calopterygid species Caliphaea hermannkunzi sp. nov. (holotype ♂ China, Yunnan Province, Lufeng County, Chuxiong City, Gaofeng village, 10 June 2019) is described and illustrated for both sexes and compared with its named congeners, from which it differs in the colour pattern of synthorax and the structure of the male anal appendages.